QUANTITATIVE STRUCTURE-ACTIVITY RELATIONSHIP ANALYSIS OF CURCUMIN AND ITS DERIVATIVES AS GST INHIBITORS BASED ON COMPUTATIONAL CHEMISTRY CALCULATION - Enade Perdana Istyastono; Sudibyo Martono; Harno Dwi Pranowo; Iqmal Tahir (Universitas Gadjah Mada, 2003)
The Quantitative Structure-Activity Relationship (QSAR) study was established on curcumin and its derivatives as glutathione S-transferase(s) (GSTs) inhibitors using atomic net charges as the descriptors. The charges were resulted by semiempirical AM1 and PM3 quantum-chemical calculations using computational chemistry approach. The inhibition activity was expressed as the concentration that gave 50% inhibition of GSTs activity (IC50). The selection of the best QSAR equation models was determined by multiple linear regression analysis. This research was related to the nature of GSTs as multifunctional enzymes, which play an important role in the detoxification of electrophilic compounds, the process of inflammation and the effectivity of anticancer compounds.The result showed that AM1 semiempirical method gave better descriptor for the construction of QSAR equation model than PM3 did. The best QSAR equation model was described by :log 1/IC50 = -2,238 - 17,326 qC2' + 1,876 qC4' + 9,200 qC6'The equation was significant at 95% level with statistical parameters : n = 10, m = 3, r = 0,839, SE = 0,254, F = 4,764, F/Ftable = 1,001.